SEPARATE STOCKS OF RED SNAPPER EXPLOITATION AND MANAGEMENT IN THE INDONESIAN SECTOR OF THE ARAFURA SEA - Badrudin Badrudin; Aisyah Aisyah (Indonesian Fisheries Research Journal, 2009)
Red snapper resources in the Arafura Sea have been effectively exploited by the industrial scale of bottom long line, fish trawl and shrimp trawl fisheries. Research activities carried out by the ACIAR-RCCF revealed that there were genetic similarity of the three red snapper species between the Australian and lndonesian sectors of the Arafura Sea"